Latitudinal Variation into the Macrofaunal Assemblages Associated to Zostera noltei Seagrass along the Atlantic Coast of Morocco - Oussama Bououarour; Soilam Boutoumit; Reda El Kamcha; Hocein Bazairi (International Journal of Zoology)
Large-scale research on seagrass-associated benthic fauna is very important for future regional marine conservation. In our study, we investigated spatial and latitudinal variation of benthic macroinvertebrate assemblages associated to Zostera noltei Hornemann, 1832 beds from five semi-enclosed coastal systems (SECSs) ranging from 23°N to 34°N along the Atlantic coast of Morocco. Overall, 17,320 individuals were reported as belonging to 96 taxa. The ecological community descriptors differ significantly at the level of the site. Specific richness showed an inconsistent significant pattern with latitude. The multivariate analyses of the assemblage’s composition showed 57% of total variation observed in benthic assemblages, while the PERMANOVA analysis confirmed that this variation is significant at the level of the site. According to DistLM results, variations in belowground biomass, and percentage of mud, were the important predictor variables explaining this variation along the large scale of the studied SECS. However, such patterns could be related to other factors such as habitat heterogeneity and regional, biogeographic, and anthropogenic factors. The present study marked the first attempt on broad-scale ecological research of seagrass beds in Morocco and offers baseline data for planning the broad-scale conservation of biodiversity in seagrass beds that remain suffering from multiple human-induced threats such as coastal developments and climate change.